AV junction ablation and conduction system pacing for patients with permanent atrial fibrillation and heart failure - Julian Wei Ee, Tong; Chan, En Ze; Chung, Bui Khiong; Ling, Hwei Sung; Chow, Han Bing; Khor, How Kiat; Andy Tze Yang, Ko; Chiang, Kit Hou; Leong, Lai Kuan; Pang, Ing Xiang; Cheah, Cheng Foong; Esteban Yu Hern, Chin; et al. (Elsevier B.V., 2024)
Strict and regular rate control with atrioventricular junction ablation (AVA) and biventricular pacemaker has been shown to reduce mortality and heart failure (HF) hospitalization in patients with atrial fibrillation (AF) and heart failure. However, whether AVA and conduction system pacing (CSP) also improves the clinical outcomes is unknown.